Assessment of natural radioactivity in maize and estimation of concomitant dose to nigerian via ingestion pathway - Yarima, Mudassir Hassan; Khandaker, Mayeen Uddin; Nadhiya, Aishath; Olatunji, Michael Adekunle (Oxford University Press, 2019)
Uranium, thorium and potassium are the most abundant naturally occurring radioactive materials (NORMs) found in soils and other environmental media including foodstuffs. Since the human exposures to NORMs is an unavoidable phenomenon, in such a way that they can easily find their way to human being via food chain, detailed knowledge on their presence in foodstuffs is necessary to assess the radiation dose to the population. Thus, the present study concerns the assessment of natural radioactivity in maize, a staple foodstuff for Nigerian, via HPGe gamma-ray spectrometry. Activity concentrations (Bq/kg) in the maize samples were found to be in the range of 6.1 ± 0.6-8.2 ± 1.3, 2.2 ± 0.4-5.1 ± 0.7 and 288 ± 16-401 ± 24 for 226Ra, 232Th and 40K, respectively. Measured data for 226Ra and 232Th show below the world average values of 67 Bq/kg and 82 Bq/kg, respectively, while the activity of 40K exceeds the global average of 310 Bq/kg. The annual effective dose via the maize consumption was found to be far below the UNSCEAR recommended ingestion dose limit of 290 μSv/y, and the estimated lifetime cancer risk show lower than the ICRP (1991) cancer risk factor of 2.5 × 10-3 based on the additional annual dose limit of 1 mSv for general public, thus pose no adverse health risk to the Nigerian populace. © 2019 The Author(s).